Influence of nanoparticles on melting and solidification during a Directed Energy Deposition process analysed by simulation. Issue 1 (1st January 2023) - Zheng, G; Laqua, R; Rey, P; Salgueiro, M; Gipperich, M; Riepe, J; Jakumeit, J
Abstract: Additive Manufacturing is a strategic tool for industrial applications. When large size structural parts are targeted, high deposition rates are important and Directed Energy Deposition (DED) is a preferred technique. A metal wire is melted by laser light and deposit on a substrate or already solidified material. Due to the small size of the melting zone, a detailed experimental analysis of the process is very difficult and simulation is an important tool to understand the manufacturing process and the influence of process and material parameter. Here the influence of the nanocomposite reinforcement on the deposition process are investigated by simulation single line tracks. A three-phase melting and solidification simulation methodology has been used to investigate the melting and solidification during DED printing of single line tracks of different wire materials. The approach uses the finite-volume method and arbitrary polyhedral control volumes to solve the governing equations. Heating of the wire by laser light is tackled using a volumetric heat source describing the specific absorption of the laser power by the metal wire. The influence of melting and solidification on the initially uniform nanocomposite distribution during the printing process is simulated using a Lagrangian approach. Firstly, simulations for steel ST 52-3 (1.0570) were performed for different process parameter settings and compared to experimental results of deposition width, height and form to validate the simulation approach. The method is then applied to Ti6Al4V wires with and without nanocomposites added to the wire material. Adding nanocomposites changes the melting and solidification behaviour of the wire materials. The influence of these changes of the material properties on the deposition process under different process conditions is analysed by simulation.